A GENRE ANALYSIS OF STUDENTS’ WRITING HORTATORY EXPOSITION TEXT AT ELEVENTH GRADE OF SENIOR HIGH SCHOOL - kardi nurhadi; Tubagus Ade Rahmat Hidayat (Wiralodra English Journal, 2019)
The objective of this study is to know how the students’ write hortatory exposition text on using generic structure and language features at eleventh grade of senior high school in Indramayu. This study utilized descriptive qualitative research using genre analysis by Hyland (2004) as research design. The data were obtained by collecting writing assignment. The writer took 20 students of XI-6 MIPA of SMAN 2 Indramayu as the participant. The texts were analyzed in term of generic structure and language features in students’ writing hortatory exposition which were undertaken by Gerot and Wignell (1994). The result showed that the students still got difficulty in writing generic structure. The students did not write generic structure completely as suggested. Mostly, they did not write recommendation in their hortatory exposition. Meanwhile, in language features, mostly did not complete their sentence by putting mental and material process. Therefore, it can be concluded that the students do not understand to write hortatory exposition in good generic structure and language features. The teacher should teach hortatory exposition by explaining and guide them carefully especially for composing recommendation for generic structure and mental process as well as material process for language features. Hence, both of them are crucial to write and organize the text. Hopefully, the students could improve their macro skills in writing.